2015
DOI: 10.1111/mpp.12291
|View full text |Cite
|
Sign up to set email alerts
|

Polycistronic artificial miRNA‐mediated resistance to Wheat dwarf virus in barley is highly efficient at low temperature

Abstract: Infection of Wheat dwarf virus (WDV) strains on barley results in dwarf disease, imposing severe economic losses on crop production. As the natural resistance resources against this virus are limited, it is imperative to elaborate a biotechnological approach that will provide effective and safe immunity to a wide range of WDV strains. Because vector insect-mediated WDV infection occurs during cool periods in nature, it is important to identify a technology which is effective at lower temperature. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…The multi‐targeting of plant viruses through artificial sRNAs was first achieved with transgenes expressing multiple amiRNAs from different precursors in cis (Ai et al ., ; Kung et al ., ) or in trans (Lafforgue et al ., ), or from a single polycistronic precursor (Fahim et al ., ; Kis et al ., ), and more recently with transgenes expressing multiple syn‐tasiRNAs from TAS1c (Carbonell and Daros, ; Carbonell et al ., ) or TAS3a precursors (Chen et al ., ), although neither the durability of the resistance nor the comparison with single targeting was systematically studied. Here, we analyzed the anti‐TSWV effects of two artificial sRNA constructs in parallel, one expressing an amiRNA and another expressing four syn‐tasiRNAs, stably expressed in S. lycopersicum .…”
Section: Discussionmentioning
confidence: 99%
“…The multi‐targeting of plant viruses through artificial sRNAs was first achieved with transgenes expressing multiple amiRNAs from different precursors in cis (Ai et al ., ; Kung et al ., ) or in trans (Lafforgue et al ., ), or from a single polycistronic precursor (Fahim et al ., ; Kis et al ., ), and more recently with transgenes expressing multiple syn‐tasiRNAs from TAS1c (Carbonell and Daros, ; Carbonell et al ., ) or TAS3a precursors (Chen et al ., ), although neither the durability of the resistance nor the comparison with single targeting was systematically studied. Here, we analyzed the anti‐TSWV effects of two artificial sRNA constructs in parallel, one expressing an amiRNA and another expressing four syn‐tasiRNAs, stably expressed in S. lycopersicum .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a multiplex amiRNA in which five miR395s in the polycistronic miRNA backbone were replaced with amiRNAs from different Wheat streak mosaic tritimovirus (WSMV) genome regions conferred immunity to WSMV in transgenic plants (Fahim et al, 2012). Similarly, the polycistronic precursor of miR171 was used to produce three amiRNAs that targeted conserved segments in the Wheat dwarf mastrevirus (WDV) genome (Kis et al, 2016). Even though amiRNAs-derived resistance has not been reported in begomoviruses, it is likely that this approach would generate resistance in these viruses, especially if the amiRNA is designed to target the Rep gene, which is the only gene indispensable for viral replication.…”
Section: New Genomic Approaches In the Control Of Cmgsmentioning
confidence: 99%
“…Resistance was assessed over two generations. The same polycistronic type of vector, which was based on a barley miRNA precursor backbone and targeted different conservative sequences of Wheat dwarf virus ( WDV ), conferred barley resistance to the virus at low temperature (Kis et al, 2016). Recent research indicated that synthetic/artificial trans-acting siRNAs (syn-tasiRNAs) carrying multiple virus resistance cassettes might be more effective than amiRNA for enhanced antiviral defense (Carbonell et al, 2016; Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%